Worker protests in post-communist Romania and Ukraine : Striking with tied hands - Varga, Mihai (Book collections on Project MUSE., 2014)
This title studies why and how successful forms of workers' interest representation could emerge in a hostile context. The post-communist context makes it difficult for workers and trade unions to mobilise, pose threats to employers, and break out of their political isolation. But initial fieldwork uncovered many instances of worker groups and trade unions that overcame such difficulties, something that led to this overarching research question: What specific strategies can succeed in advancing the rights and living standards of workers?